A distributed, multi‐hop, adaptive, tree‐based energy‐balanced routing approach. (5th April 2019) - Arora, Vishal Kumar; Sharma, Vishal; Sachdeva, Monika
Summary: To accomplish the primary objective of data sensing and collection of wireless sensor networks (WSN), the design of an energy efficient routing algorithm is very important. However, the energy constrained sensing nodes along with the intrinsic properties of the (WSN) environment makes the routing a challenging task. To overcome this routing dilemma, an improved distributed, multi‐hop, adaptive, tree‐based energy‐balanced (DMATEB) routing scheme is proposed in this paper. In this scheme, a relay node is selected in view of minimum distance and high energy from a current sensing node. Further, the parent node is chosen among the selected relay nodes on the basis of high residual energy and less power consumption with due consideration of its associated child nodes. As each sensing node itself selects its parent among the available alternatives, the proposed scheme offers a distributive and adaptive approach. Moreover, the proposed system does not overload any selected parent of a particular branch as it starts acting as a child whenever its energy lowers among the other available relay nodes. This leads to uniform energy utilization of nodes that offers a better energy balance mechanism and improves the network lifespan by 20% to 30% as compared with its predecessors. Abstract : A current sensing node "C" selects its own set of relay nodes based on the distance to base station (BS) and residual energy (RE). The sensor nodes that shortened the distance to BS and having higher RE than C node will act as relay nodes of C node. Further, a node "P" either having high RE or consumes less power with/without consideration of its associated child nodes among the selected relay nodes will be selected to act as parent node.